2003
DOI: 10.1046/j.1365-3024.2003.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile of Plasmodium falciparum‐specific T cells in non‐immune malaria patients

Abstract: CD3+ T cells are important sources of both pro- and anti-inflammatory cytokines during Plasmodium falciparum malaria. We studied the frequency of interleukin-2 (IL-2), gamma interferon (IFN-gamma), tumour necrosis factor-alpha (TNF-alpha) and IL-10 expressing CD3+ cells in 10 non-immune malaria patients with uncomplicated malaria and in one patient with cerebral malaria after P. falciparum-specific and non-specific mitogenic stimulation. Analysis by fluorescence-activated cell sorting was performed after drug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…It has been previously demonstrated that preferentially IFN-c producing, type 1 effector cells but not type 2 effectors undergo rapid apoptotic cell death when restimulated, which might explain to some extent the selective loss of PBMC derived IFN-c production in TB patients reported in earlier studies [53]. Second, we routinely use costimulation with MAb CD28 in addition to PPD to increase the yield of antigen-specific immune responses in T cells [49], which might overcome the reported downregulation of type 1 responses by MTB secretory antigen-differentiated and matured dendritic cells (DC), that display altered surface densities of co-stimulatory molecules [54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been previously demonstrated that preferentially IFN-c producing, type 1 effector cells but not type 2 effectors undergo rapid apoptotic cell death when restimulated, which might explain to some extent the selective loss of PBMC derived IFN-c production in TB patients reported in earlier studies [53]. Second, we routinely use costimulation with MAb CD28 in addition to PPD to increase the yield of antigen-specific immune responses in T cells [49], which might overcome the reported downregulation of type 1 responses by MTB secretory antigen-differentiated and matured dendritic cells (DC), that display altered surface densities of co-stimulatory molecules [54].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in 5 ml ultra culture medium (UCM) (Bio Whittaker, Walkersville, MD) supplemented with L-glutamine (2 mM/l; Sigma, St. Louis, MI), gentamicin (170 mg/l; Sigma) and 2-mercaptoethanol (3.5 µl/l; Merck, Darmstadt, Germany) for 18 h at 37°C in 5% CO 2 and stimulated with or without PPD (Statens Serum Institute, Copenhagen, Denmark) at a final concentration of 10 µg/ml. In order to amplify TCR signaling and to facilitate the initial phase of T cell activation the co-stimulatory MAb CD28 (Pharmingen, San Diego, CA) was added at a final concentration of 5 µg/ml to some wells [49]. Brefeldin A (10 µg/ml final concentration, Sigma) was added after 6 h to block protein secretion.…”
Section: Detection Of Ppd-specific T Cell Cytokine Expression By Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…[191]). In contrast, recall responses are markedly increased in malaria patients following a first clinical episode [192][193][194][195]. Indeed, even subclinical infections are sufficient to induce robust IFN-␥ responses to pRBC in previously naïve donors [19,20,42].…”
Section: Dynamics Of Ifn-␥ Responses In Relation To Exposurementioning
confidence: 99%